PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK PERLINDUNGAN VARIETAS TANAMAN JAGUNG MANIS TALENTA - Luthfiatul Fikria (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT Indonesia as a state of law certainly wants a just and prosperous life and livelihood for its people in accordance with the norms and rules that have been established and apply in society. Legal protection essentially everyone has the right to legal protection, almost all legal relationships must receive protection from the law, one of which is the legal protection given to Plant Variety Protection. The establishment of a legal protection, namely in the event of a violation of the rights of the holder of the Plant Variety Protection right. The research method includes the type of normative juridical research using a statutory approach and a conceptual approach. The conclusions drawn by the author in this thesis are first, the form of legal protection for the right holder of the sweet corn variety of talent is carried out externally and internally. Second, to compensate PVP rights holders if their actions pollute the reputation of PVP rights holders. Efforts to resolve the dispute if there is a violation of the rights of the sweet corn plant variety of talent is to be able to file a civil lawsuit in the District Court.